2014
DOI: 10.3996/082013-jfwm-057
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Passive and Active Acoustic Sampling for a Bat Community Impacted by White-Nose Syndrome

Abstract: In the summers of 2011 and 2012, we compared passive and active acoustic sampling for bats at 31 sites at Fort Drum Military Installation, New York. We defined active sampling as acoustic sampling that occurred in 30-min intervals between the hours of sunset and 0200 with a user present to manipulate the directionality of the microphone. We defined passive sampling as acoustic sampling that occurred over a 12-h period (1900-0700 hours) without a user present and with the microphone set in a predetermined direc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
25
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 22 publications
(26 reference statements)
0
25
0
Order By: Relevance
“…Maximizing detection rates is essential in the face of WNS-related bat declines and the increasing level of effort required to detect a present species (Coleman et al 2014). For example, we found that detection probability decreased with increasing wind speed for the eastern red bat, which is likely a function of microphone interference.…”
Section: Discussionmentioning
confidence: 73%
“…Maximizing detection rates is essential in the face of WNS-related bat declines and the increasing level of effort required to detect a present species (Coleman et al 2014). For example, we found that detection probability decreased with increasing wind speed for the eastern red bat, which is likely a function of microphone interference.…”
Section: Discussionmentioning
confidence: 73%
“…Live traps had the greatest LTD and lowest POD compared with the other 2 techniques, highlighting the inefficiency of traditional techniques versus the effectiveness of noninvasive techniques to obtain detection or nondetection data, as has been observed with numerous other wildlife species (e.g., Hackett et al , Coleman et al , McDonald et al ). Although our study was of a shorter duration than most live‐trapping studies within the southern Appalachians, captures/trap night were similar to other regional live‐trap efforts (Hackett , Menzel et al ; C. A. Diggins, unpublished data).…”
Section: Discussionmentioning
confidence: 85%
“…We calculated 1 technician‐hour at US$15 (Coleman et al ). For both camera traps and acoustics, we did not count download time of data toward our cost or effort analysis because data downloading did not require full attention of technicians (e.g., data download may take 45 min, but configuration took the technician ≤5 min).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations